Coastal Microbial Communities Disrupted During the 2018 Hurricane Season in Outer Banks, North Carolina - Garrison, Cody E.; Roozbehi, Sara; Mitra, Siddhartha; Corbett, D. Reide; Field, Erin K. (Frontiers in Microbiology, 2022)
Hurricane frequencies and intensities are expected to increase under warming climate scenarios, increasing potential to disrupt microbial communities from steady-state conditions and alter ecosystem function. This study shows the impact of hurricane season on microbial community dynamics within the barrier island system of Outer Banks, North Carolina. We found that the passage of two sequential energetic hurricanes in 2018 (Florence and Michael) were correlated with shifts in total and active (DNA and RNA) portions of bacterial communities but not in archaeal communities, and within surface waters but not within the sediment. These microbial community shifts were distinct from non-hurricane season conditions, suggesting significant implications for nutrient cycling in nearshore and offshore environments. Hurricane-influenced marine sites in the coastal North Atlantic region had lower microbial community evenness and Shannon diversity, in addition to increased relative abundance of copiotrophic microbes compared to non-hurricane conditions. The abundance of functional genes associated with carbon and nitrogen cycling pathways were also correlated with the storm season, potentially shifting microbial communities at offshore sites from autotroph-dominated to heterotroph-dominated and leading to impacts on local carbon budgets. Understanding the geographic- and system-dependent responses of coastal microbial communities to extreme storm disturbances is critical for predicting impacts to nutrient cycling and ecosystem stability in current and future climate scenarios.